1988
DOI: 10.1172/jci113774
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective aldosterone deficiency on acidification in nephron segments of the rat inner medulla.

Abstract: Mineralocorticoid plays a role in urinary acidification and acid-base balance, but the response of the inner medulla to aldosterone has not been elucidated. A model of selective aldosterone deficiency (SAD) with hyperkalemia and hyperchloremic metabolic acidosis was employed to assess segmental acidification by measuring in situ pH, titratable acidity (TA) and total ammonia (Am). Hydrogen ion secretion was also examined as a function of the increment in in situ Pco2 in the collecting duct during bicarbonate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A role for corticosteroid hormones in the renal regulation ofacid-base balance has been proposed in previous studies, in which acute and chronic acid loading were shown to increase the plasma aldosterone concentration in humans, rats, and dogs (15)(16)(17)(18) and the plasma glucocorticosteroid concentration in dogs and rats ( 14, 16) but not in humans (15,18). Although aldosterone is known to stimulate proton secretion in collecting ducts (reviewed in reference 28), to what extent the acidosis-induced increment in the circulating aldosterone level contributes to the renal response against acidosis remains to be established. The presence of circulating glucocorticosteroids has been shown to be necessary for a normal adaptive increase in renal ammonia and phosphate excretion in response to acute and chronic metabolic acidosis in the rat (17,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 97%
“…A role for corticosteroid hormones in the renal regulation ofacid-base balance has been proposed in previous studies, in which acute and chronic acid loading were shown to increase the plasma aldosterone concentration in humans, rats, and dogs (15)(16)(17)(18) and the plasma glucocorticosteroid concentration in dogs and rats ( 14, 16) but not in humans (15,18). Although aldosterone is known to stimulate proton secretion in collecting ducts (reviewed in reference 28), to what extent the acidosis-induced increment in the circulating aldosterone level contributes to the renal response against acidosis remains to be established. The presence of circulating glucocorticosteroids has been shown to be necessary for a normal adaptive increase in renal ammonia and phosphate excretion in response to acute and chronic metabolic acidosis in the rat (17,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 97%
“…The outer medullary outer and inner stripes secrete H+ regardless of the acid-base status of the animal (17,24,31,32), and the rates of secretion do not increase with acid-loading (26,31,32). The inner medulla also has H+ secretion (33)(34)(35)(36)(37), which is augmented by acidemia (33,35,36).…”
Section: Introductionmentioning
confidence: 99%
“…Key words: collecting duct acidification * countercurrent multiplication -hyperkalemic metabolic acidosis * loop of Henle * urinary ammonia excretion Results of these experiments were reported in preliminary form at the 22nd Annual Meeting of the American Society of Nephrology (1990. Changes in systemic potassium balance have an important influence on urinary net acid excretion, predominantly through effects on urinary ammonium excretion (1)(2)(3).' Potassium retention and clinical hyperkalemia are associated with a decrease in urinary ammonium excretion that is thought to contribute to the metabolic acidosis that accompanies a variety of pathologic conditions, such as mineralocorticoid deficiency and chronic renal insufficiency (2)(3)(4)(5)(6)(7)(8). Based on the observations that an increase in extracellular potassium concentration decreased ammonium synthesis by renal cortical slices, renal cortical tubule suspensions, and isolated, perfused proximal tubules (9-1 1 ), it had generally been assumed that the decrease in urinary ammonium excretion with hyperkalemia was the result ofa decrease in ammonium production and secretion by the proximal tubule.…”
Section: Introductionmentioning
confidence: 99%